Exhibición y distribución de cortometrajes de propaganda de los Estados Unidos en Argentina en los años ’40: el programa de 16 mm de la OCIAA - Alejandro Kelly Hopfenblatt (Nuevo mundo - Mundos Nuevos, 2020)
In the 1940’s, numerous countries throughout Latin America undertook activities related to the exhibition of propaganda short films. Working within the Good Neighbor Policy, the Office of the Coordinator of Inter-American Affairs (OCIAA) developed an ambitious program that covered an extended institutional and territorial map. By reaching distant geographical spots, it aimed to present audiovisual materials related both to the World War and to the American Way of Life.This essay presents the main guidelines of the 16 mm Program by analyzing its organizational structure, the films it exhibited and the audiences’ experience. While this program’s operations have been studied in other countries such as Chile or Brazil, its activities in Argentina have yet to be considered. Therefore, based on documentation that refers to the organization and practice of OCIAA’s screenings, this essay aims to reconstruct its history in Argentina and propose analytical frameworks for further and deeper studies.